Young adults’ satisfaction regarding their dining experience in casual dining restaurants in Hatfield, Pretoria - wkasapila@yahoo.co.uk (University of Pretoria, 2013)
Dissertation (MConsSc (Food Management))--University of Pretoria, 2006.